2015
DOI: 10.1111/ajgw.12147
|View full text |Cite
|
Sign up to set email alerts
|

Effect of ageing of sweet Sherry wines obtained from cvs Muscat and Pedro Ximénez on ethyl carbamate concentration

Abstract: Background and Aims:Ethyl carbamate (EC) is a known carcinogen that has been found in wines. The aims of this study were: (i) to study the effect of fermentation under different enological conditions on the EC concentration in sweet Sherry wines made from the two grape cultivars, Muscat and Pedro Ximénez, during three consecutive vintages (2008)(2009)(2010); and (ii) to investigate the evolution of EC concentration during ageing in oak and in stainless steel. Methods and Results: Before and during ageing, the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 32 publications
0
5
0
Order By: Relevance
“…From a sensory point of view [ 62 , 63 ], the sweet Muscat wines fermented at low temperature (< 10 °C) with S. bayanus yeast without nutrients and pectolytic enzymes, were characterized by intense citrus and floral notes and were the best rated, while the ones obtained using nutrients were granted the lowest scores. In a follow-up study [ 64 ], the same authors observed that the use of S. bayanus significantly decreased ethyl carbamate content in the wines—a compound declared to be carcinogenic—while the use of nutrients and pectolytic enzymes increased its content levels. PX wines, with their characteristic amino acid profile, presented lower concentrations of this compound than Muscat wines.…”
Section: Study Of the Aroma Of Natural Sweet Winesmentioning
confidence: 99%
“…From a sensory point of view [ 62 , 63 ], the sweet Muscat wines fermented at low temperature (< 10 °C) with S. bayanus yeast without nutrients and pectolytic enzymes, were characterized by intense citrus and floral notes and were the best rated, while the ones obtained using nutrients were granted the lowest scores. In a follow-up study [ 64 ], the same authors observed that the use of S. bayanus significantly decreased ethyl carbamate content in the wines—a compound declared to be carcinogenic—while the use of nutrients and pectolytic enzymes increased its content levels. PX wines, with their characteristic amino acid profile, presented lower concentrations of this compound than Muscat wines.…”
Section: Study Of the Aroma Of Natural Sweet Winesmentioning
confidence: 99%
“…From a sensory point of view [62,63], the sweet Muscat wines fermented at low temperature (< 10 • C) with S. bayanus yeast without nutrients and pectolytic enzymes, were characterized by intense citrus and floral notes and were the best rated, while the ones obtained using nutrients were granted the lowest scores. In a follow-up study [64], the same authors observed that the use of S. bayanus significantly decreased ethyl carbamate content in the wines-a compound declared to be carcinogenic-while the use of nutrients and pectolytic enzymes increased its content levels. PX wines, with their characteristic amino acid profile, presented lower concentrations of this compound than Muscat wines.…”
Section: β-Damascenonementioning
confidence: 94%
“…The type of aging also plays an important role in the formation of ethyl carbamate: when the process was carried out in oak barrels, the content of ethyl carbamate in wine was higher (57.4 µg/L) than when using stainless steel tanks (47.3 µg/L). This difference may be due to favorable conditions for the development of microorganisms during the aging of wine in oak barrels due to limited oxygen access and, consequently, an increase in the concentration of ethyl carbamate precursors [8,82].…”
Section: Technological Factors Affecting the Formation Of Ethyl Carba...mentioning
confidence: 99%